Thermodynamics and physics of matter. Volume I - Rossini, Frederick D. [ed.] (High speed aerodynamics and jets propulsion;, 1955)
Fundamentals of thermodynamics - Fundamental physics of gases - Thermodynamic properties of real gases and mixtures of real gases - The transport properties of gases and gaseous mixtures - Critical phenomena - Properties of liquids and liquid solutions - Properties of solids and solid solutions - Relaxation phenomena in gases - Gases at low densities - The thermodynamics of irreversible processes.